2011
DOI: 10.1091/mbc.e11-03-0198
|View full text |Cite
|
Sign up to set email alerts
|

Axonal filopodial asymmetry induced by synaptic target

Abstract: Early nerve–muscle interaction that leads to neuromuscular junction formation is mediated by axonal filopodia that are oriented preferentially toward the muscle as a result of target-derived basic fibroblast growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 40 publications
9
41
0
Order By: Relevance
“…Here spinal neurons expressing GFP, WTp120ctn, or Δp120 were exposed to control or bFGF-added medium for 6 h and then examined live. Treatment with bFGF enhanced the formation of filopodia in GFP-neurons (Figure 6, A and B, vs. A′ and B′), as seen previously using neurons expressing no exogenous proteins (Li et al. , 2011), and bFGF also increased the number of SV puncta in these neurons (Figure 6, C and C′).…”
Section: Resultssupporting
confidence: 84%
“…Here spinal neurons expressing GFP, WTp120ctn, or Δp120 were exposed to control or bFGF-added medium for 6 h and then examined live. Treatment with bFGF enhanced the formation of filopodia in GFP-neurons (Figure 6, A and B, vs. A′ and B′), as seen previously using neurons expressing no exogenous proteins (Li et al. , 2011), and bFGF also increased the number of SV puncta in these neurons (Figure 6, C and C′).…”
Section: Resultssupporting
confidence: 84%
“…WT-FGFR1- and TR-FGFR1-neurons had more and less filopodia than GFP-neurons, respectively, and both displayed a marked decrease in the extension of filopodia preferentially towards muscle cells, much as in our previous work [14]. Overexpression of bFGF in muscle slightly increased the growth of filopodia towards muscle in WT-FGFR1- but not in TR-FGFR1-neurons (Figure 6G), which again indicated that normal FGFR1 signaling in neurons is needed for bFGF to elicit filopodial growth.…”
Section: Resultssupporting
confidence: 76%
“…First, to examine if there is autocrine activation of TrkB – as a result of the secretion of BDNF from spinal neurons themselves – TrkB-Fc was used as a scavenger to remove BDNF from the medium. Previously we found that cessation of axonal growth upon target recognition is accompanied by increased generation of axonal filopodia [14]. Thus, we examined the effect of TrkB-Fc on the number of axonal filopodia in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The preparation has been used widely to study the biophysical properties of presynaptic ion channels and the regulation of transmitter release [5][6][7][8] . In addition, the preparation has lent itself to other uses including the study of neurite outgrowth and synaptogenesis [9][10][11][12] …”
mentioning
confidence: 99%
“…The preparation has been used widely to study the biophysical properties of presynaptic ion channels and the regulation of transmitter release [5][6][7][8] . In addition, the preparation has lent itself to other uses including the study of neurite outgrowth and synaptogenesis [9][10][11][12] , molecular mechanisms of neurotransmitter release [13][14][15] , the role of diffusible messengers in neuromodulation 16,17 , and in vitro synaptic plasticity [18][19] .…”
mentioning
confidence: 99%